Detectors for selective registration of charged particles and gamma-quanta - Ryzhikov, V.; Starzhinskiy, N.; Katrunov, K.; Gal’chinetskiy, L.; Chernikov, V.; Zelenskaya, O.; Krivonosov, E.; Litvinov, L.; Galkin, S.; Loseva, E. (Вопросы атомной науки и техники, 2002)
A new design is proposed and described of a combined detector (CD) for simultaneous detection of charged particles and gamma-quanta. The CD comprises a single crystalline plate of ZnSe(Te) placed onto the output window of a scintillating transparent light transducer made of CsI(Tl) and Al₂O₃(Ti) in the shape of truncated pyramid. The CsI(Tl) light transducer is used to create an additional channel for detection of gamma-radiation, as well as for protecting the photodiode from the penetrating radiation. It is shown that introduction of such light transducer does not worsen the energy characteristics of ZnSe(Te). Separate detection of alpha- and gamma-radiation has been achieved under simultaneous excitation by ²³⁹Pu (ZnSe(Te), Ra = 6 %) and ²⁴¹Am (CsI(Tl), Rγ = 20 %). The use of selective optical filters allows separation of the peaks of total absorption (p.t.a.) in the case of their superposition. Пропонується конструкція комбінованого детектора (КД) для одночасної реєстрації заряджених часток і γ-квантів. КД складається з монокристалічної платівки ZnSe(Te), яка розташована на вхідному вікні сцинтилюючого прозорого світловоду з CsI(Tl) та Al₂O₃(Ti) у вигляді зрізаної піраміди. Світловод з CsI(Tl) використовується для створення додаткового каналу реєстрації γ-випромінення, а також захищає фотодіод від впливу проникаючої радіації. Показано, що використання такого світловоду не погіршує енергетичні характеристики ZnSe(Te). Отримана роздільна реєстрація α-часток та γ-випромінення в умовах одночасного збудження ZnSe(Te) частками ²³⁹Pu (Ra=6 %) и CsI(Tl) частками ²⁴¹Am (Rγ=20 %). Використання селективного оптичного фільтра дозволяє розділяти піки повного поглинання (п.п.п) у випадку їх взаємного накладення. Предложена и описана конструкция комбинированного детектора (КД) для одновременной регистрации заряженных частиц и γ-квантов. КД состоит из монокристаллической пластинки ZnSe(Te), расположенной на входном окне сцинтиллирующего прозрачного световода из CsI(Tl) и Al₂O₃(Ti) в виде усеченной пирамиды. Световод из CsI(Tl) используется для создания дополнительного канала регистрации γ-излучения, а также защищает фотодиод от воздействия на фотоприемник проникающей радиации. Показано, что использование такого световода не ухудшает энергетические характеристики ZnSe(Te). Получена раздельная регистрация α- и γ-излучения при одновременном возбуждении ²³⁹Pu (ZnSe(Te)) (Ra=6 %) и ²⁴¹Am (CsI(Tl)) (Rγ=20 %). Использование селективного оптического фильтра позволяет разделять пики полного поглощения (п.п.п) в случае их наложения друг на друга.